Generation of solid waste during the pandemia: Diagnosis on the beaches of Camburi and Camburizinho in São Sebastião-SP city - Pokorni, Mariana de Souza; Kniess, Cláudia Terezinha; Nascimento, Ana Paula Branco do (Technical and Scientific Journal Green Cities, 2021)
The  amount of solid waste is a problem that humanity has been facing. The North Coast of São Paulo is no different, the high influence of tourism coupled with the fast population growth, makes this situation worse every day. The city of São Sebastião has several instruments necessary for the urban planning of the city and its management. There are specific laws on the Solid Waste (RS) theme, in addition to the Land Use and Occupation Law and the Master Plan, which provides for aspects of infrastructure and the proposition of housing and environmental policies. Despite all these tools, the ineffective management of urban waste, as well as port economic activities and tourism make this issue still cause concern on the Brazilian coast. The present work referred to a study, through quanti-qualitative collection and analysis, in addition to secondary data through bibliographic searches in books, academic websites and pertinent legislation. In order to make a current diagnosis on the procriation of RS, during the pandemic on the beaches of Camburi and Camburizinho in the city of São Sebastião. It was noticed that the flow of the floating population during the time of the pandemic had a significant growth, and consequently, the increase in the amount of SR. If each one takes care of their garbage and mainly decreases the consumption of disposables, the number of residues has the possibility of minimizing. KEYWORDS: Solid waste. Pandemic. São Sebastião